JESZCZE O TAJEMNICY LORDA SINGELWORTH. MIĘDZY IRONIĄ A AUTOIRONIĄ - Skalińska, Ewangelina (Colloquia Litteraria, 2019)
Tajemnica lorda Singelworth once again. Between Irony and Autoirony The article uses autoirony as the fundamental interpretative key to Norwid’s Tajemnica lorda Singelworth. The author puts the analyzed text in biograp- hical, epistolary, and publishing contexts, which produces a new way to understand the novella. This new interpretation suggests reading of Tajemnica as Norwid’s play with his earlier style as well as a attempt at autoironic representation of the textual subject’s attitude.